ChemInform Abstract: Synthesis of Hexahydroisoindole‐3a‐carboxylates by IMDA Reaction of Morita—Baylis—Hillman Adduct‐Derived Dienes Bearing a Z‐Alkenyl Tether. Issue 6 (11th February 2014) - Kim, Ko Hoon; Lee, Sangku; Lee, Junseong; Go, Min Jeong; Kim, Jae Nyoung
Abstract An intramolecular Diels—Alder (IMDA) reaction of Morita—Baylis—Hillman adduct‐derived dienes bearing a Z‐alkenyl dienophile tether affords hexahydroisoindole‐3a‐carboxylates in excellent yields and stereoselectivity.